Rethinking East Asian peace: the perils of over-deterrence and minilateralism - He, Kai (Australian journal of international affairs, 2025)
The world is in crisis. The ongoing wars in Ukraine and the Middle East have made the relative peace in East Asia more precious and puzzling. While Asia's unique balance of power, developmental model, and cultural heritage have played a role in maintaining this relative peace, an often-overlooked factor is the peace-oriented multilateral arrangements established in the post-Cold War era. However, the intensifying competition between the US and China has led to over-deterrence, with both nations resorting to excessive measures to deter each other, as well as to the proliferation of security minilaterals in the region. It is time to encourage strategic restraint, constrain security minilaterals, and revive multilateralism in the region to maintain the exceptional peace in Asia.